Література канадських українців. Мирна Косташ: у пошуках національної ідентичності - Шадріна, Тетяна Володимирівна; Shadrina, T. V. (My University, 2016)
Стаття торкається проблеми формування національної ідентичності в сучасному багатонаціональному суспільстві. На прикладі двох творів документальної прози канадської письменниці українського походження М. Косташ аналізується “гібридна ідентичність”, яка виникає на перехресті двох культур: рідної та набутої. Шлях, яким прямує етнічна письменниця до своєї національної самоідентифікації, пролягає через реінтеграцію в історію, культуру, мову її народу. The article deals with the problem of formation of national identity in the modern multinational society. Taking two works of non-fi ction as a pattern by a Canadian author of Ukrainian origin M. Kostash we analyze the «hybrid identity”, which occurs at the junction of two cultures: native and acquired. The ways which the ethnic writer chooses towards her own national identity lies through re-integration into history, culture, language of her people. In fact we move towards cross-cultural or multi-ethnic societies. Under such circumstances identity is considered to be not a stable entity, but a process. It’s changeable, multiple and fragmentary (a postmodernist view). So, we observe the situation where the Ukrainian-Canadian author demonstrates the construction of the ambivalent identity. Starting as a writer with a distinct Canadian identity (she is a representative of the third generation of Ukrainians in Canada) in her book “All of Baba’s children” Myrna Kostash explores the history of surviving the Ukrainian immigrants in the Canadian prairies. But coming to the next book “Bloodlines: A Journey into Eastern Europe” gradually she begins to feel a Ukrainian also. Thus the journey to the motherland of her ancestors, their history and language provokes the crisis of Kostash’s identity which is keenly revealed in her texts.
Literature of canadian ukrainians. Myrna Kostash: looking for national identity
Keywords: іммігранти; гібридна ідентичність; етнічна/національна ідентичність; україно-канадці; українська громада; мультикультуралізм; інтеграція; асиміляція; immigrants; hybrid identity; ethnic/national identity; Ukrainian-Canadians; Ukrainian community; multiculturalism; integration; assimilation